Recent advances in the development of bitter gourd seed oil: from chemical composition to potential applications - Huiling Wang; Xiaoyan Shuai; Shuxin Ye; Rui Zhang; Muci Wu; Sijia Jiang; Yubao Li; Dong Wu; Jingren He (Critical Reviews in Food Science and Nutrition, 2023)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

A robust rice yield estimation framework developed by grading modeling and normalized weight decision-making strategy using UAV imaging technology - Rui Yang; Jun Zhou; Xiangyu Lu; Jianxun Shen; Huizhe Chen; Mengyuan Chen; Yong He; Fei Liu (Computers and Electronics in Agriculture, 2023)

Utilization of halophytes in saline agriculture and restoration of contaminated salinized soils from genes to ecosystem: Suaeda salsa as an example - Chen Yang Li; Rui He; Chang Yan Tian; Jie Song (Marine Pollution Bulletin, 2023)

Longitudinal wastewater surveillance of four key pathogens during an unprecedented large-scale COVID-19 outbreak in China facilitated a novel strategy for addressing public health priorities–A proof of concept study - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiqiang Deng; Fenglan He; Xiaotong Jiang; Lixin Shen (Water Research, 2023)

Increased m6A-RNA methylation and demethylase FTO suppression is associated with silica-induced pulmonary inflammation and fibrosis - Yunyi Xu; Liqun Wang; Rui Qian; Manyu Zhao; Xuxi Chen; Donglei Sun; Ye Wang; Weibo Cheng; Yiping Chen; Qiurong He; Yi Dai; Yuqin Yao (Toxicology, 2023)

Current overview of impact analysis and risk assessment of urban pluvial flood on road traffic - Haiqi He; Rui Li; Jianzhong Pei; Jean-Pascal Bilodeau; Guojing Huang (Sustainable Cities and Society, 2023)

Factors regulating interaction among inorganic nitrogen and phosphorus species, plant uptake, and relevant cycling genes in a weakly alkaline soil treated with biochar and inorganic fertilizer - Hongyan Li; Rui Ren; Hongyu Zhang; Guixiang Zhang; Qiusheng He; Zhiwang Han; Shuhui Meng; Yanli Zhang; Xiaohui Zhang (Science of The Total Environment, 2023)

Micro-nano bubble water with potassium fertigation improves strawberry yield and quality by changing soil bacterial community - Jian Wang; Qiu He; Kai Cao; Bo Zhou; Xiaoli Niu; Duo Wang; Rui Chen; Zhen Zheng (Rhizosphere, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Influence of extractable organic components on shale wettability: Dongyuemiao member of Jurassic Ziliujing formation in the Fuxing area, Eastern Sichuan Basin - Weihang Zhang; Rui Yang; Zhiliang He; Hanyong Bao; Hui Yu; Shuling Xiong; Yuanjia Han; Qinhong Hu; Sheng He (Marine and Petroleum Geology, 2023)

Application of alkaline sludge based LDHs in Cd and Cu polluted wastewater remediation: Process and mechanism - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xiao He; Xin Chuai; Shaoping Wang; Jin Wang (Journal of Water Process Engineering, 2023)

Enhanced biological wastewater treatment supplemented with anaerobic fermentation liquid of primary sludge - Lin Li; Qiqi Liao; Caihong Liu; Tanglong Zhang; Chang Liu; Ziwei Chen; Rui Gao; Qiang He (Journal of Environmental Management, 2023)

Edible electrospun zein nanofibrous scaffolds close the gaps in biofilm formation ability between microorganisms - Meng-Xin Hu; Fei He; Cheng-Kai Tu; Zhe-Xin Chen; Hui Teng; Xin Shao; Ge-Rui Ren; Ya-Xin Guo (Food Bioscience, 2023)

Recent advances in stability improvement of anthocyanins by efficient methods and its application in food intelligent packaging: A review - Rui Tang; Yong He; Kai Fan (Food Bioscience, 2023)

Characteristics of dissolved organic matter in point-source wastewaters at a petrochemical plant: Molecular constituents and contributions to the influent of wastewater treatment plant - Yue Kou; Baiyu Yang; Juntao Jiang; He Sun; Rui Zhang; Zhuoyu Li; Qinghong Wang; Quan Shi; Chunmao Chen (Environmental Research, 2023)

An interval water demand prediction method to reduce uncertainty: A case study of Sichuan Province, China - Xinyu Xia; Bin Liu; Rui Tian; Zuli He; Suyue Han; Ke Pan; Jingjing Yang; Yiting Zhang (Environmental Research, 2023)

Improving wildfire occurrence modelling by integrating time-series features of weather and fuel moisture content - Xingwen Quan; Wenli Wang; Qian Xie; Binbin He; Víctor Resco de Dios; Marta Yebra; Miao Jiao; Rui Chen (Environmental Modelling & Software, 2023)

Chemical constituents from Mytilaria laosensis Lec. leaves and branches - Xiaofang Ye; Yingxin Liang; Boxuan Liao; Chen Ni; Huaqiang Lu; Rui He; Cuixian Zhang; Hui Xu; Jinchang Yang (Biochemical Systematics and Ecology, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Quantitative Estimation on Methane Storage Capacity of Organic-Rich Shales from the Lower Silurian Longmaxi Formation in the Eastern Sichuan Basin, China - Xiaowen Guo; Tao Luo; Tian Dong; Rui Yang; Yuanjia Han; Jizheng Yi; Sheng He; Zhiguo Shu; Hanyong Bao (Journal of Earth Science, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

Toward the development of smart capabilities for understanding seafloor stretching morphology and biogeographic patterns via DenseNet from high-resolution multibeam bathymetric surveys for underwater vehicles - Rui Nian; Shasha Liu; Zongcan Lu; Xiaoyu Li; Shidong Ren; Yuqi Qian; Qiuying Li; Guotong He; Kexin Shi; Guoyao Zhang; Lina Zang; Luyao Li; et al. (Frontiers in Marine Science, 2023)
The increasing use of underwater vehicles facilitates deep-sea exploration at a wide range of depths and spatial scales. In this paper, we make an initial attempt to develop online computing strategies to identify seafloor categories and predict biogeographic patterns with a deep learning-based architecture, DenseNet, integrated with joint morphological cues, with the expectation of potentially developing its embedded smart capacities. We utilized high-resolution multibeam bathymetric measurements derived from MBES and denoted a collection of joint morphological cues to help with semantic mapping and localization. We systematically strengthened dominant feature propagation and promoted feature reuse via DenseNet by applying the channel attention module and spatial pyramid pooling. From our experiment results, the seafloor classification accuracy reached up to 89.87%, 82.01%, and 73.52% on average in terms of PA, MPA, and MIoU metrics, achieving comparable performances with the state-of-the-art deep learning frameworks. We made a preliminary study on potential biogeographic distribution statistics, which allowed us to delicately distinguish the functionality of probable submarine benthic habitats. This study demonstrates the premise of using underwater vehicles through unbiased means or pre-programmed path planning to quantify and estimate seafloor categories and the exhibited fine-scale biogeographic patterns.

Two truxinate derivatives and a phenyldilactone from the leaves of Castanopsis eyrei - Ya-feng Wang; Nao Pang; Zhen-hua Liang; Yong-lin Huang; Rui-jie He; Bing-yuan Yang; Zhang-bin Liu (Natural Product Research, 2023)

Aluminum soap nanoparticles-lignin powder form phase-selective gelator as an efficient sorbent for oils/water separation - Suwan Cui; Bohao Qi; Hao Liu; Xiaojun Sun; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Mutai Bao (Chemosphere, 2023)

Developmental and neurobehavioral toxicity of 2,2′-methylenebis(6-tert-butyl-4-methylphenol) (antioxidant AO2246) during the early life stage of zebrafish - Yinan Chai; Donglai Sheng; Xiaowei Ji; Yanlong Meng; Feihao Shen; Rui He; Runjia Ma; Yuying Wang (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Assessment of cruise ship decarbonization potential with alternative fuels based on MILP model and cabin space limitation - Wenxian Zhang; Yuan He; Nianyuan Wu; Fuzheng Zhang; Danni Lu; Zekun Liu; Rui Jing; Yingru Zhao (Journal of Cleaner Production, 2023)

Camel milk peptides alleviate hyperglycemia by regulating gut microbiota and metabolites in type 2 diabetic mice - Yongjin Zhang; Ju Wang; Wupeng Ge; Yuxuan Song; Rui He; Zhi Wang; Lili Zhao (Food Research International, 2023)

Selenium speciation and volatile flavor compound profiles in the edible flowers, stems, and leaves of selenium-hyperaccumulating vegetable Cardamine violifolia - Yan Ma; Jinjing Yin; Jingyi Wang; Xin Liu; Jingren He; Rui Zhang; Shen Rao; Xin Cong; Yin Xiong; Muci Wu (Food Chemistry, 2023)

Reducing airborne transmission of SARS-CoV-2 by an upper-room ultraviolet germicidal irradiation system in a hospital isolation environment - Haiyang Liu; Zhijian Liu; Junzhou He; Chenxing Hu; Rui Rong; Hao Han; Lingyun Wang; Desheng Wang (Environmental Research, 2023)

pH-responsive polyacrylic acid chemical cross-linking for end-of-life reverse osmosis membrane rejuvenation - Yuyan Hai; Xin Wen; Rui Ma; Can He; Xue Yang; Rihua Xiong; Jingyun Chen; Qiaoyi Sun (Desalination, 2023)

Constructing MoS2-SnS heterostructures on N-doped carbon nanosheets for enhanced catalytic conversion of polysulfides in lithium-sulfur batteries - Junpu Zhang; Wen Xi; Feng Yu; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Chemical Engineering Journal, 2023)

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Dysregulation of MicroRNAs Derived from Plasma Extracellular Vesicles in Schizoaffective Disorder - Rui Chen; Junxia Shi; Hongguang Yang; Minzhe Zhang; Qiutong Chen; Qiqiang He (Molecular Neurobiology, 2023)

Glutathione Might Attenuate Arsenic-Induced Liver Injury by Modulating the Foxa2-XIAP Axis to Reduce Oxidative Stress and Mitochondrial Apoptosis - Hua Zhang; Baiming Jin; Lele Liu; Haonan Li; Xiujuan Zheng; Mingqi Li; Rui He; Kewei Wang (Biological Trace Element Research, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

A new modified pterocarpan glycoside from Sophora flavescens - Yan Lin; Jing-Jing Li; Lei He; Qi-Rui Li; Qing-De Long; Xu Zhang; Zhu Zeng (Natural Product Research, 2023)

Prophylactic norepinephrine combined with 6% hydroxyethyl starch (130/0.4) co-load infusion for preventing postspinal anesthesia hypotension during cesarean section: a randomized, controlled, dose-finding trial - Lei Guo; Xiangsheng Xiong; Rui Qin; Zhenzhou Li; Yongqiang Shi; Wei Xue; Ling He; Shuqin Ma; Yi Chen (DARU Journal of Pharmaceutical Sciences, 2023)

Analysis of spatial and temporal variation of vegetation NPP in Daning River Basin and its driving forces - Wenqian Bai; Li He; Zhengwei He; Xueman Wang; Yang Zhao; Rui Qu; Fang Luo; Xin Chen; Zhifei Wang; Ming Liu (International Journal of Remote Sensing, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

A new norditerpenoid and other components from Ajuga macrosperma and their bioactivity - Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Hong-Ping He; Rui Yang; Hua-Yi Jiang (Phytochemistry Letters, 2023)

Membrane flux response technology for early warning of initial surface scaling in membrane distillation - Zhijie Yuan; Rui Zhao; Guoxin Sun; Peiyu Li; Shaohua Yin; Guoli Zhou; Gaohong He; Xiaobin Jiang (Journal of Water Process Engineering, 2023)

Melt-blown fiber felt for efficient all-weather recovery of viscous oil spills by Joule heating and photothermal effect - Bohao Qi; Nuo Wang; Xin Hu; Suwan Cui; Hao Liu; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Yang Li; Mutai Bao (Journal of Hazardous Materials, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Effects of microplastics on functional genes related to CH4 and N2O metabolism in bacteriophages during manure composting and its planting applications - Wei-Kang Deng; Jun-Liang He; Jing-Yuan Chen; Rui-Ting Wu; Si-Cheng Xing; Xin-Di Liao (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Anaerobic biodegradation of anthraquinone dye reactive black 19 by a resuscitated strain Bacillus sp. JF4: Performance and pathway - Qian Zhang; Yuyang Wang; Mayada Jamal; Rui Wang; Qiuyang He; Faqian Sun; Hongjun Lin; Xiaomei Su (Journal of Environmental Chemical Engineering, 2023)

Microbial resistance stability of rice straw biochar with vermiculite modification: A novel insight into persistent free radicals and pore structure - Yuxue Liu; Rui Wang; Lili He; Cunjun Li; Yuying Wang; Haohao Lu; Shengmao Yang (Journal of Environmental Chemical Engineering, 2023)

The metal-organic frameworks as unique platform for photocatalytic CO2 conversion to liquid fuels - Xiahong Xu; Kangle Xie; Junjie Hu; Suijun Liu; Hong Zhong; He-Rui Wen (Journal of Environmental Chemical Engineering, 2023)

Comprehensive investigation of milk oligosaccharides in different mammalian species and the effect of breed and lactation period on sheep milk oligosaccharides - Haiyan Wang; Minghui Zhang; Yucui Huo; Xiuxiu Cui; Rui He; Bei Han; Zhongfu Wang; Yuxuan Song; Xin Lv; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Acetylcholine (ACh) enhances Cd tolerance through transporting ACh in vesicles and modifying Cd absorption in duckweed (Lemna turionifera 5511) - Lin Yang; Xu Ma; Yuhan Guo; Yuman He; Yunwen Yang; Wenqiao Wang; Ziyi Xu; Zhaojiang Zuo; Ying Xue; Rui Yang; Bing Han; Jinsheng Sun (Environmental Pollution, 2023)

Orbitally-paced coastal sedimentary records and global sea-level changes in the early Permian - Ren Wei; Zhijun Jin; Rui Zhang; Mingsong Li; Yongyun Hu; Xiangwu He; Shuai Yuan (Earth and Planetary Science Letters, 2023)

ZIF-8-derived hollow carbon polyhedra with highly accessible single Mn-N6 sites as peroxymonosulfate activators for efficient sulfamethoxazole degradation - Yue Zhao; Rui Gao; He Wang; Yanping Sun; Xiaohui Zhan; Lei Chen; Junyan Liu; Huixiang Shi (Chemical Engineering Journal, 2023)

Experimental Study of the Rock Cutting Mechanism with PDC Cutter Under Confining Pressure Condition - Weiji Liu; Hongxing Deng; Xiaohua Zhu; Rui Li; Chao He (Rock Mechanics and Rock Engineering, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Genome-wide analysis of long noncoding RNA profiles in pseudorabies-virus-infected PK15 cells - Jian-guo Dong; Ming-rui Chen; Dan Rao; Ning Zhang; Shuhai He; Lei Na (Archives of Virology, 2023)

Editorial: Noise and vibrations in offshore wind farms and their impact on aquatic species - Rui He; Apostolos Tsouvalas; Xiaomei Xu; Lijun Dong (Frontiers in Marine Science, 2023)

Study on the correlation and interaction between metals and dyslipidemia: a case–control study in Chinese community-dwelling elderly - Zhongyuan Zhang; Rui Wang; Pei He; Yuqing Dai; Siyu Duan; Meiyan Li; Zhuoheng Shen; Xiaoyu Li; Jian Sun (Environmental Science and Pollution Research, 2023)

Spatiotemporal variations and dominated environmental parameters of nitrous oxide (N2O) concentrations from cascade reservoirs in southwest China - Chiquan He; Rui Qi; Haiyue Feng; Zhenzhen Zhao; Fushun Wang; Daoyuan Wang; Feifei Wang; Xueping Chen; Pu Zhang; Siliang Li; Yuanbi Yi (Environmental Science and Pollution Research, 2023)

Analysis of the factors influencing the water-energy-food system stress in China - Boyu Jin; Rui Shi; Silin Chen; Yue He; Minjuan Zhao (Environmental Science and Pollution Research, 2023)

Effects of atrazine on microbial metabolic limitations in black soils: Evidence from enzyme stoichiometry - Tiancong Gao; Haixia Tian; Ziqi Wang; Jing Shi; Rui Yang; Fang Wang; Leilei Xiang; Yunchao Dai; Mallavarapu Megharaj; Wenxiang He (Chemosphere, 2023)

Adjusting effects of pyrolytic volatiles interaction in char to upgrade oil by swelling waste nylon-tire - Rui Huang; Qiangqiang Ren; Jialin Zhang; Limo He; Sheng Su; Yi Wang; Long Jiang; Jun Xu; Song Hu; Jun Xiang (Waste Management, 2023)

Influence of freeze–thaw cycles on mechanical properties of moraine soils - Enxi Qiu; Qiaoling He; Qiuling Chen; Xiwang Sun; Rui Zhang; Mengfei Qu; Xusheng Wan (Transportation Geotechnics, 2023)

Centrifugal model test study on deformation characteristics of deep, thick fillings in giant karst cave tunnels under different construction processes - Rui Su; Qian Su; Minqi Dong; Chenfang He; Yuchao Zheng; Xun Wang; Yanfei Pei (Transportation Geotechnics, 2023)

VOC transport in an occupied residence: Measurements and predictions via deep learning - Rui Zhang; Xinglei He; Jialong Liu; Jianyin Xiong (Science of The Total Environment, 2023)

Integrating data dependent and data independent non-target screening methods for monitoring emerging contaminants in the Pearl River of Guangdong Province, China - Rui Wang; Yanan Yan; He Liu; Yanxi Li; Meng Jin; Yuqing Li; RiZhu Tao; Qianghua Chen; Xuguang Wang; Bo Zhao; Danping Xie (Science of The Total Environment, 2023)

Effects of the launch parameters on trans-phase stability performance and mechanism for submarine-launched missiles model - Qibin Zhuang; Huanbin Zhang; Chenhong Zhao; Xingyu He; Yu Liu; Zhirong Liu; Shuping Li; Rui Zhu; Dezhi Wu (Ocean Engineering, 2023)

Distinct urban-rural gradients of air NO2 and SO2 concentrations in response to emission reductions during 2015–2022 in Beijing, China - Tao He; Yang Tang; Rui Cao; Nan Xia; Binghe Li; Enzai Du (Environmental Pollution, 2023)

Tailoring zincophilicity via amorphous Se-rich selenides coating for stable Zn anode - Guoquan Jiang; Rui Xue; Linxin He; Junchao Zhu; Nan Qiu; Yuan Wang (Chemical Engineering Journal, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

Effects of superabsorbent polymers (SAPs) incorporated with organic and inorganic fertilizer on the water and nutrient retention of soil in rare earth mine tailing areas - Yanzi He; Zhiyuan Tian; Rui Ma; Yin Liang; Xuchao Zhu; Lili Qu (Journal of Soils and Sediments, 2023)

Nafamostat mesilate prevented caerulein-induced pancreatic injury by targeting HDAC6-mediated NLRP3 inflammasome activation - Peng Chen; Li-Jun Zhao; Ling Huang; Wen-Qi He; Ying-Rui Tang; Yi Liu; Jian-Dong Ren (Inflammation Research, 2023)

Semi-supervised interlayer intelligent recognition method - Shixiang Jiao; Jun Zhao; Yufei He; Shixuan Zhao; Zhenguan Wu; Tianyi Zeng; Rui Zhang (Earth Science Informatics, 2023)

Reduced Survival and Resistance of Rhodotorula mucilaginosa Following Inhibition of Pigment Production by Naftifine - Nur Fazleen Binti Idris; Qianying Jia; He Lu; Yanan Guo; Yang Wang; Rui Hao; Zeng Tu (Current Microbiology, 2023)

Impact of rhizosphere priming on soil organic carbon dynamics: Insights from the perspective of carbon fractions - Hao Cui; Chaoyang Mo; Pengfei Chen; Rui Lan; Chao He; Jingdong Lin; Zhenhui Jiang; Jingping Yang (Applied Soil Ecology, 2023)

Quantifying the effects of urban development intensity on the surface urban heat island across building climate zones - Tianxing He; Rui Zhou; Qun Ma; Chunlin Li; Dan Liu; Xuening Fang; Yina Hu; Jun Gao (Applied Geography, 2023)

Kinetic and thermodynamic analysis on preparation of belite-calcium sulphoaluminate cement using electrolytic manganese residue and barium slag by TGA - Weilong He; Rui Li; Yanping Yang; Yu Zhang; Dengpan Nie (Environmental Science and Pollution Research, 2023)

Holocene climatic controls on flooding regime along the Ussuri River in Northeast Asia - Zhenqing Zhang; Lin Li; Rui Yin; Lu Zhang; Kai Yi; He Ji; Haijiao Yin; Lili Huo (Science of The Total Environment, 2023)

Effects of gums on 3D printing performance of Pleurotus eryngii powder - Anqi He; Juan Xu; Qiuhui Hu; Liyan Zhao; Gaoxing Ma; Lei Zhong; Rui Liu (Journal of Food Engineering, 2023)

A new insight into the polar lipid composition in mature breast milk and ewe milk with comparative lipidomics analysis - Shuangshuang Wang; Yuxuan Song; Rui He; Guanli Du; Lei Zhang; Bangjun Zhang; Jiaying Zhang; Lili Zhao; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Heat waves accelerate the spread of infectious diseases - Xinbo Lian; Jianping Huang; Han Li; Yongli He; Zhi Ouyang; Songbo Fu; Yingjie Zhao; Danfeng Wang; Rui Wang; Xiaodan Guan (Environmental Research, 2023)

Effects of different water-cooled heat sinks on the cooling system performance in a data center - Wei He; Jifang Zhang; Hailong Li; Rui Guo; Shengchun Liu; Xiaohui Wu; Jie Wei; Yulin Wang (Energy and Buildings, 2023)

Selective pollutant degradation with a novel persulfate activation cell resistant to environmental interference - Hui-Shan Meng; Shu-Zhen He; Mei-Mei Wang; Jia-Rui Xi; Jia-Tai Wen; Hong-Wei Luo; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

Preparation of bio-jet fuels by a controllable integration process: Coupling of biomass fermentation and olefin polymerization - Yuehui Luo; Rui Zhang; Yuting He; DanFeng Lou; Rui Zhu; Can Zhu; Minghui Fan; Quanxin Li (Bioresource Technology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

LncRNA BBOX1-AS1 Contributes to the Progression of Esophageal Carcinoma by Targeting the miR-361-3p/COL5A1 Axis - Yu-Hai Lu; Dong-Sheng He; Ying Li; Hong Wang; Rui-Dong Ma (Biochemical Genetics, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

Removal of per- and polyfluoroalkyl substances by nanofiltration: Effect of molecular structure and coexisting natural organic matter - Caihong Liu; Ye Shen; Xiaoqing Zhao; Ziwei Chen; Rui Gao; Qingyang Zuo; Qiang He; Jun Ma; Yue Zhi (Journal of Hazardous Materials, 2023)

Mechanism for regulation of a forward osmosis membrane by the SA/UiO-66-NH2 composite interlayer and the resulting lithium ion concentration performance - Miaolu He; Yushuang Li; Leihao Feng; Jiaqi Wang; Ze Liu; Lei Wang; Jin Wang; Rui Miao; Xudong Wang (Journal of Cleaner Production, 2023)

Formation and preservation of ultra-deep liquid petroleum in the Ordovician sedimentary succession in Tarim Basin during the neotectonic phase - Feng Li; Xiuxiang Lü; Guangyou Zhu; Jianfa Chen; Rui Wang; Zhenghui Wu; Tao He; Nan Xue (Journal of Asian Earth Sciences, 2023)

Systematic exploration of transcriptional responses of interspecies interaction between Karenia mikimotoi and Prorocentrum shikokuense - Jian-Wei Zheng; Guo-Hui He; Rui-Xia Xu; Xiang Wang; Hong-Ye Li; Wei-Dong Yang (Harmful Algae, 2023)

Eastward extension of the Solonker Suture beneath the central Songliao Basin, NE China: Evidence from a deep seismic reflection profile - Ming-Rui Li; Rui Gao; Jian-Bo Zhou; Simon A Wilde; He-Sheng Hou; Xiao-Fan Deng (Gondwana Research, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

Soil variables and reflected light revealed the plasticity of grape and wine composition: Regulation of the flavoromics under inner row gravel covering - Meng-Bo Tian; Wan-Hui Ma; Nong-Yu Xia; Jing Peng; Rui-Qi Hu; Chang-Qing Duan; Fei He (Food Chemistry, 2023)

Obliquity forcing of continental aquifers during the late Paleozoic ice age - Ren Wei; Mingsong Li; Rui Zhang; Yongyun Hu; James G. Ogg; Guoyong Liu; He Huang; Xiangwu He; Shuai Yuan; Qifan Lin; Zhijun Jin (Earth and Planetary Science Letters, 2023)

Nanostructured carboxylated-wood aerogel membrane for high-efficiency removal of Cu (II) ions from wastewater - Wen He; Jizhou Cao; Feiyu Guo; Zhihao Guo; Peiguo Zhou; Rui Wang; Shuang Liang; Qunyan Pang; Bairen Wei; Yue Jiao; Tripti Singh; Qiliang Fu (Chemical Engineering Journal, 2023)

A hierarchical In2O3@ZIF-67 architecture with upgraded CO2 photoreduction performances - Ying-Jie Wang; Bing He; Dejun Ma; Rui Li; Yabo Xie; Jian-Rong Li (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Microorganisms, their residues, and soil carbon storage under a continuous maize cropping system with eight years of variable residue retention - Xuefeng Zhu; Hongtu Xie; Michael D. Masters; Yichao Rui; Yu Luo; Hongbo He; Xudong Zhang; Chao Liang (Applied Soil Ecology, 2023)

Water stable isotope characteristics and water use strategies of co-occurring plants in ecological and economic forests in subtropical monsoon regions - Junjie Dai; Xinping Zhang; Li Wang; Rui Wang; Zidong Luo; Xinguang He; Zhiguo Rao (Journal of Hydrology, 2023)

Solid-state fermentation alters the fate of red kidney bean protein during buccal and gastrointestinal digestion: Relationship with cotyledon cell wall integrity - Wenjing Sun; Jie He; Haijun Wang; Qiuqin Zhang; Wei Li; Xin Rui (Food Chemistry, 2023)

Fe/Ni layered double hydroxide biocatalysts inhibit tumor growth through ROS and ferroptosis signaling pathway - Qiwen Pan; Fei Lin; Ruiqi Liu; Yilin Li; Xinyue Zhang; Rui Luo; Lingling Cai; Yang Liu; Wuguo Deng; Liru He (Chemical Engineering Journal, 2023)

Chemical constituents from Ajuga macrosperma Wall. ex Benth. (Lamiaceae) and their chemotaxonomic significance - Hua-Yi Jiang; Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Ming-Ming Li; Rui Yang; Hong-Ping He (Biochemical Systematics and Ecology, 2023)

Elemental Geochemical Distribution of the Jurassic Yan'an Formation in the Ningdong Coalfield and its Controlling Effect on Coal Reservoir Properties - Jincheng Ye; Yafei Zhang; Wei He; Rui Tao; Shu Tao; Shida Chen; Yi Cui; Qi Wang (Natural Resources Research, 2023)

The Impact of Long-term Phosphorus Fertilization on Soil Aggregation and Aggregate-Associated P Fractions in Wheat-Broomcorn Millet/Pea Cropping Systems - Asif Khan; Shengli Guo; Wang Rui; Binghui He; Tianyang Li; Umer Mahmood (Journal of Soil Science and Plant Nutrition, 2023)

Asymmetric effects of daytime and nighttime warming on alpine treeline recruitment - Hang Shi; Quan Zhou; Rui He; Quanfa Zhang; Haishan Dang (Global Change Biology, 2023)
Trees at their upper range limits are highly sensitive to climate change, and thus alpine treelines worldwide have changed their recruitment patterns in response to climate warming. However, previous studies focused only on daily mean temperature, neglecting the asymmetric influences of daytime and nighttime warming on recruitments in alpine treelines. Here, based on the compiled dataset of tree recruitment series from 172 alpine treelines across the Northern Hemisphere, we quantified and compared the different effects of daytime and nighttime warming on treeline recruitment using four indices of temperature sensitivity, and assessed the responses of treeline recruitment to warming‐induced drought stress. Our analyses demonstrated that even in different environmental regions, both daytime and nighttime warming could significantly promote treeline recruitment, and however, treeline recruitment was much more sensitive to nighttime warming than to daytime warming, which could be attributable to the presence of drought stress. The increasing drought stress primarily driven by daytime warming rather than by nighttime warming would likely constrain the responses of treeline recruitment to daytime warming. Our findings provided compelling evidence that nighttime warming rather than daytime warming could play a primary role in promoting the recruitment in alpine treelines, which was related to the daytime warming‐induced drought stress. Thus, daytime and nighttime warming should be considered separately to improve future projections of global change impacts across alpine ecosystems.

Associations between multiple urinary metals and the risk of hypertension in community-dwelling older adults - Siyu Duan; Rui Wang; Pei He; Jian Sun; Huifang Yang (Environmental Science and Pollution Research, 2023)

Sources and historical records of metal(loid)s in river sediments from an agricultural tributary of Tuojiang river: Evidence from geochemical analyses and Pb isotope - Fen Xu; Rui Yang; Hong Wang; Xiaoxia He; Weiwei Li; Yao Wei; Linlin Bao; Jianfei Yuan; Hongjin Tong (Chemosphere, 2023)

Different characteristics of soil CH4 emissions and methanogenic communities in paddy fields under gradually and abruptly elevated CO2 concentrations - Yuanyuan Wang; Zhenghua Hu; Lidong Shen; Guihua Lu; Rui Cao; Kezhi Zheng; Chao Liu; Zhurong Wu; Shuqi He (Soil Biology and Biochemistry, 2023)

Depositional-diagenetic process and their implications for pore development of Wufeng-Longmaxi shales in the Jiangdong block, Fuling shale gas field, SW China - Kefei Chen; Rui Yang; Hanyong Bao; Tian Dong; Aoqi Jia; Qinhong Hu; Xiaowen Guo; Sheng He (Marine and Petroleum Geology, 2023)

Heterogeneity of molecular-level and photochemical of dissolved organic matter derived from decomposing submerged macrophyte and algae - Jia He; Lixin Jiao; Guoqiang Zhi; Xue Wu; Yan Yang; Shuai Ding; Jinlong Zheng; Zhi Shao; Rui Xia (Journal of Environmental Management, 2023)

Abiotic transformation of synthetic progestins in representative soil mineral suspensions - Xingjian Yang; Rui Wang; Zhili He; Xiong Dai; Xiuping Jiang; He Liu; Yongtao Li (Journal of Environmental Sciences, 2023)

Comparison of Pivot Profile, CATA, and Pivot-CATA for the sensory profiling of instant black coffee - Shiqin Wang; Keng Hong Ng; Kwan Hiu Yee; Yihang Tang; Rui Meng; Wenmeng He (Food Quality and Preference, 2023)

Preparation and characterization of V-type starch nanoparticles by an oil-water interface method - Hao Lu; Xiaoyang He; Yang Qin; Na Ji; Lei Dai; Liu Xiong; Rui Shi; Tao Wang; Qingjie Sun (Food Hydrocolloids, 2023)

Combined methods elucidate the multi-organ toxicity of cylindrospermopsin (CYN) on Daphnia magna - Zhongshi He; Youxin Chen; Da Huo; Jin Gao; Yewei Xu; Rui Yang; Yiming Yang; Gongliang Yu (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Effect of KMnO4/pH adjustment of extracellular polymeric substances under waste activated sludge on sludge dewatering - Weiliang Pan; Jiaoni Li; Xun Zhang; Shan Liang; Yinghao Kang; Rui Deng; Li Gu; Qiang He (Environmental Science and Pollution Research, 2023)

Forward osmosis membrane doped with water-based zirconium fumarate MOFs to enhance dye pollutant removal and membrane antifouling performance - Miaolu He; Leihao Feng; Qi Cui; Yushuang Li; Jiaqi Wang; Jiani Zhu; Lei Wang; Xudong Wang; Rui Miao (Environmental Science and Pollution Research, 2023)

Study on mutual harmless treatment of electrolytic manganese residue and red mud - Jing Zhang; Rui Li; Yu Zhang; Weilong He; Junjie Yang; Yu Wang (Environmental Science and Pollution Research, 2023)

A novel pollination robot for kiwifruit flower based on preferential flowers selection and precisely target - Changqing Gao; Leilei He; Wentai Fang; Zhenchao Wu; Hanhui Jiang; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Evaluation method of rowing performance and its optimization for UAV-based shot seeding device on rice sowing - Wei Liu; Zhiyan Zhou; Xuelang Xu; Qingyu Gu; Shuaishuai Zou; Weizhuo He; Xiwen Luo; Junhao Huang; Jianqin Lin; Rui Jiang (Computers and Electronics in Agriculture, 2023)

Assessing the effects of short-term traffic restriction policies on traffic-related air pollutants - Xiao-Rui Fang; Xing-Hang Zhu; Xing-Zhou Li; Zhong-Ren Peng; Hu Qingyao; Hong-Di He; AJ Yuan Chen; Huang Cheng (Science of The Total Environment, 2023)

Characteristics of silicon and phytolith distribution in bamboo (Ferrocalamus strictus): variations between different organs and ages - Rui Xu; Honglan He; Huijun Guo; Fangwei Zhu; Shuguang Wang; Cefeng Dai; Xiaofeng Zheng; Dongbo Xie; Haoming Li; Changming Wang; Hui Zhan (Review of Palaeobotany and Palynology, 2023)

A crack characterization model for subsea pipeline based on spatial magnetic signals features - Jiaxing Xin; Rui Li; Jinzhong Chen; Run-kun Lu; Chang Liu; Zhengda Su; Renyang He; Hongwu Zhu (Ocean Engineering, 2023)

Origin of biotite-rich xenoliths in the Eocene Beiya porphyry: Implications for upper-crustal Au remobilization and formation of giant porphyry Au systems in a collisional setting - Ye Zhou; Zengqian Hou; Rui Wang; Bo Xu; Noreen J. Evans; Wenyan He; Yuanchuan Zheng; Jiaxi Zhou (Lithos, 2023)

Estimating the maximum vegetation coverage and productivity capacity supported by rainwater resources on the Loess Plateau - Yao Li; Baoqing Zhang; Rui Shao; Tongxuan Su; Xuejin Wang; Lei Tian; Chansheng He (Journal of Hydrology, 2023)

Multi-model analysis of historical runoff changes in the Lancang-Mekong River Basin – Characteristics and uncertainties - Yuxin Li; Aifang Chen; Ganquan Mao; Penghan Chen; Hao Huang; Hong Yang; Zifeng Wang; Kai Wang; He Chen; Ying Meng; Rui Zhong; Pengfei Wang; et al. (Journal of Hydrology, 2023)

Rapid and sensitive quantification of cyclamate in beverages by miniature microplasma optical emission spectrometry - Jiang Jing; Siyu He; Jiahui Yang; Rui Yang; Yao Lin; Chengbin Zheng (Food Chemistry, 2023)

Modulation of the interfacial properties of TiN coatings to generate Rigid-Flexible SEI for better SiO anodes - Hebang Shi; He Zhang; Rui Wang; Ming Liu; Zihan Shen; Jingbo Chen; Binbin Wu; Maoqiao Xiang; Jun Li; Huigang Zhang; Pengpeng Lv; Qingshan Zhu (Chemical Engineering Journal, 2023)

Ultra-thin hierarchical porous carbon coated metal phosphide self-assembled efficient tri-functional electrodes for overall water splitting and rechargeable zinc-air batteries - Rui He; Tuo Lu; Nengneng Xu; Guicheng Liu; Yanxing Zhang; Jinli Qiao (Chemical Engineering Journal, 2023)

Effect of aged biochar after microbial fermentation on antibiotics removal: Key roles of microplastics and environmentally persistent free radicals - Yanzhuo Zhang; Rui He; Jing Zhao; Xiaozhuan Zhang; Alexandr V. Bildyukevich (Bioresource Technology, 2023)

Effects of biochar addition towards the treatment of blackwater in anaerobic dynamic membrane bioreactor (AnDMBR): Comparison among room temperature, mesophilic and thermophilic conditions - Weiliang Pan; Honglin Ouyang; Xiuqing Tan; Shanji Yan; Ruihao Zhang; Rui Deng; Li Gu; Qiang He (Bioresource Technology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Discovery of Neoproterozoic adakitic rocks in the Eastern Tianshan (NW China) of the southern Altaids - Meng Wang; Qigui Mao; Wenjiao Xiao; He Yang; Hao Wang; Rui Li (International Journal of Earth Sciences, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Influence of Soil Plug on the Seismic Response of Bucket Foundations in Liquefiable Seabed - Xue-Qian Qu; Rui Wang; Jian-Min Zhang; Ben He (Journal of Marine Science and Engineering, 2023)
The suction installation process for bucket foundations for offshore wind turbines (OWTs) can cause the formation of soil plug within the bucket, which can affect the seismic performance of the OWT. Therefore, it is important to evaluate the influence of soil plug on the seismic performance of OWT on bucket foundations. In this study, a comprehensive set of high-fidelity solid–fluid coupled dynamic numerical simulations are conducted to analyze the seismic response of bucket foundations with a focus on the influence of soil plug and its potential mitigation. The influence of different bucket models, seabed soil densities, seabed inclination and reinforcement types, as well as soil plug removal techniques, are investigated. The results clearly show that the existence of soil plug has a significant unfavorable influence on the seismic performance of OWT on bucket foundations, especially for wide bucket foundations in mildly inclined seabeds, and should be considered in seismic design. Reinforcement methods, such as the application of an inner compartments, outer wings and inner pile, can improve the seismic performance of OWT on bucket foundations, with the application of an inner compartment being the most effective. Soil plug removal can alleviate the negative influence of soil plug, and should be adopted when possible.

Removal mechanism of tetracycline-Cr(Ⅵ) combined pollutants by different S-doped sludge biochars: Role of environmentally persistent free radicals - Yanzhuo Zhang; Rui He; Jing Zhao (Chemosphere, 2023)

Quality prediction of tractor rotary tillage based on BiConvLSTM with self-attention - Ruo-chen Li; Chang-kai Wen; Shu-yan Li; Rui Li; Hong-yu Pu; Yu Jiang; Zheng-he Song (Computers and Electronics in Agriculture, 2023)

Enhanced LiteHRNet based sheep weight estimation using RGB-D images - Chong He; Yongliang Qiao; Rui Mao; Mei Li; Meili Wang (Computers and Electronics in Agriculture, 2023)

A novel method of imposing external water pressure to explore the failure behavior of railway tunnel linings - Ben-Guo He; Rui-Hua Xue; Zhi-Qiang Zhang; Xia-Ting Feng; Chuan Wu (Tunnelling and Underground Space Technology, 2023)

Global seamless and high-resolution temperature dataset (GSHTD), 2001–2020 - Rui Yao; Lunche Wang; Xin Huang; Qian Cao; Jing Wei; Panxing He; Shaoqiang Wang; Lizhe Wang (Remote Sensing of Environment, 2023)

A critical review of adsorption isotherm models for aqueous contaminants: Curve characteristics, site energy distribution and common controversies - Qili Hu; Rui Lan; Liru He; Hengyuan Liu; Xiangjun Pei (Journal of Environmental Management, 2023)

Effects of calcination on the environmental behavior of sediments by phosphorus speciation and interface characterization - Rui Xia; Pingzhou Duan; Rui Li; Lixin Jiao; Jia He; Shuai Ding; Xue Wu (Journal of Environmental Management, 2023)

Variability of fuel consumption and CO2 emissions of a gasoline passenger car under multiple in-laboratory and on-road testing conditions - Boya Zhou; Liqiang He; Shijian Zhang; Rui Wang; Luowei Zhang; Mengliang Li; Yu Liu; Shaojun Zhang; Ye Wu; Jiming Hao (Journal of Environmental Sciences, 2023)

Experimental investigation of thermodynamic and kinetic behaviors from water vapor adsorption on four typical clay minerals - Shuling Xiong; Manfei Chen; Hui Yu; Weihang Zhang; Qinhong Hu; Sheng He; Rui Yang (Gas Science and Engineering, 2023)

Corrigendum to “Limited hydrolysis of glycosylated whey protein isolate ameliorates the oxidative and physical stabilities of conjugated linoleic acid oil-in-water emulsions” [Food Chem. 362 (2021)130212] - Meng Li; Rui Yu; Runxiao Fu; Yanting He; Zhanmei Jiang; Juncai Hou (Food Chemistry, 2023)

The structural characterization and color stabilization of the pigment protein-phycoerythrin glycosylated with oligochitosan - Yidan Zhang; Liqun Zhang; Jiangnan Hu; Zhiwei Wang; Demei Meng; He Li; Zhongkai Zhou; Rui Yang (Food Hydrocolloids, 2023)

The protective role of vitamin C on intestinal damage induced by high-dose glycinin in juvenile Rhynchocypris lagowskii Dybowski - Rui Zhu; Zongyu Liu; Minghui Lu; Xueqin Wu; Xueyuan Zhao; Hong-He Wang; Ya-Nan Quan; Li-Fang Wu (Fish & Shellfish Immunology, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Iron-based nanomaterials reduce cadmium toxicity in rice (Oryza sativa L.) by modulating phytohormones, phytochelatin, cadmium transport genes and iron plaque formation - Pingfan Zhou; Peng Zhang; Mengke He; Yu Cao; Muhammad Adeel; Noman Shakoor; Yaqi Jiang; Weichen Zhao; Yuanbo Li; Mingshu Li; Imran Azeem; Like Jia; et al. (Environmental Pollution, 2023)

Genome-wide identification and expression analysis of the cotton patatin-related phospholipase A genes and response to stress tolerance - Yunxiao Wei; Zhili Chong; Chao Lu; Kaili Li; Chengzhen Liang; Zhigang Meng; Yuan Wang; Sandui Guo; Liangrong He; Rui Zhang (Planta, 2023)

Quantitative estimation of bubble volume fraction of submarine seep plumes by modeling seismic oceanography data - Tonggang Han; Jiangxin Chen; Leonardo Azevedo; Bingshou He; Huaning Xu; Rui Yang (Journal of Oceanology and Limnology, 2023)

The Novel Fluorescent Probe Toward Yttrium(III) and its Bioimaging - Yuxin Qin; Qian Meng; Junxiong Yao; Mengyu Chen; Yajie Dong; Dashuo Chen; Shuping He; Cuibing Bai; Lin Zhang; Biao Wei; Hui Miao; Changqing Qu; et al. (Journal of Fluorescence, 2023)

Tissue-resident immune cells in the pathogenesis of multiple sclerosis - Jie Tian; Lingli Jiang; Zixiang Chen; Qingfang Yuan; Chang Liu; Longfeng He; Feng Jiang; Ke Rui (Inflammation Research, 2023)

Isolation of atrazine nanobodies enhanced by depletion of anti-carrier protein phages and performance comparison between the nanobody and monoclonal antibody derived from the same immunogen - Qingqing He; Mian Wang; Yajie Zhao; Guiyu Tan; Man Zhang; Rui Feng; Yujie Chen; Baomin Wang; Qing X. Li (Analytica Chimica Acta, 2023)

Effects of social capital on farmers’ choices of climate change adaptation behavior in Dazu District, China - Lin Li; Jianjun Jin; Rui He; Foyuan Kuang; Chenyang Zhang; Xin Qiu (Climate and Development, 2023)

Effects of varying levels of crawfish (Procambarus clarkia) shell meals on growth, fillet quality, and health of koi carp (Cyprinus carpio) - Xiaofei Cheng; Jin Xiang; Jingjing Tian; Xing Tian; Hao Wu; Xiping Yuan; Zhigang He; Min Xie; Rui Song (Aquaculture, 2023)

Utility of a non-target screening method to explore the chlorination of similar sulfonamide antibiotics: Pathways and NCl intermediates - Di Xia; He Liu; Yang Lu; Yanchen Liu; Jiahao Liang; Danping Xie; Guining Lu; Jinrong Qiu; Rui Wang (Science of The Total Environment, 2023)

The effects of salt flow on the cross-section restoration of salt-bearing fold-and-thrust belts: An example from the Kuqa depression - Wanhui He; Wei Wang; Huiwen Xie; Hongwei Yin; Dong Jia; Zhenping Xu; Haoyu Luo; Rui Yuan (Journal of Structural Geology, 2023)

A global meta-analysis of coal mining studies provides insights into the hydrologic cycle at watershed scale - Jiahui Yang; Huaixin Wei; Zelin Quan; Rui Xu; Zhaohui Wang; Hailong He (Journal of Hydrology, 2023)

Accurate combination forecasting of wave energy based on multiobjective optimization and fuzzy information granulation - Yuqi Dong; Jianzhou Wang; Rui Wang; He Jiang (Journal of Cleaner Production, 2023)

Hydrogen bond network reconstruction of lignite for efficient moisture removal via deep-eutectic-solvent-assisted hydrothermal treatment - Yujie Yu; Jianfeng Li; Rui Huang; Xianrui Yao; Yumu Tang; Yu He (Fuel, 2023)

The physicochemical properties of a starch–sodium stearoyl lactylate complex formed via annealing treatment in ethanol solutions - Xiaoyu Chen; Chaofan Wang; Xiaoyang He; Yang Qin; Lei Dai; Liu Xiong; Tao Wang; Rui Shi; Na Ji; Qingjie Sun (Food Hydrocolloids, 2023)

An interfacial gas-enrichment strategy for mitigating hydrate adhesion and blockage - Rui Ma; Senbo Xiao; Yuanhao Chang; Yuequn Fu; Jianying He; Zhiliang Zhang (Chemical Engineering Journal, 2023)

Redox of anionic and cationic radical intermediates in a bipolar polyimide COF for high-performance dual-ion organic batteries - Shuai Gu; Jingjing Chen; Rui Hao; Xi Chen; Zhiqiang Wang; Iftikhar Hussain; Guiyu Liu; Kun Liu; Qingmeng Gan; Zhiqiang Li; Hao Guo; Yingzhi Li; et al. (Chemical Engineering Journal, 2023)

SnO2/ATP catalyst enabling energy-efficient and green amine-based CO2 capture - Zhan Tan; Shangshang Zhang; Fangfang Zhao; Rui Zhang; Feiying Tang; Kuiyi You; He'an Luo; Xiaowen Zhang (Chemical Engineering Journal, 2023)

Target acquisition of anti-aging manno-oligosaccharide that triggers ECM process via TGF-β/Smads-SIRT1 signalling pathway - Liu Yang; Chengting Zi; Dingkang Chen; Jinyu Li; Rui He; Jiang-Miao Hu (Carbohydrate Polymers, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Endothelial LRP1-ICD Accelerates Cognition-Associated Alpha-Synuclein Pathology and Neurodegeneration through PARP1 Activation in a Mouse Model of Parkinson’s Disease - Rui Huang; Yuyuan Gao; Qingrui Duan; Qingxi Zhang; Peikun He; Jianing Chen; Guixian Ma; Limin Wang; Yuhu Zhang; Kun Nie; Lijuan Wang (Molecular Neurobiology, 2023)

Upregulation LncRNA MEG3 expression suppresses proliferation and metastasis in melanoma via miR-208/SOX4 - Yi Yang; Liang Jin; Juan He; Rui Wang; Yilin Wang; Jia Bai; Youbai Chen; Zhanpeng Luo (Molecular and Cellular Biochemistry, 2023)

Status, distribution, source, and risk of polychlorinated biphenyl levels in soils of five cities from the Hexi Corridor, Northwest China - Zhanrong Jia; Longmiao Yuan; Yufeng Jiang; Rui He; Wenxuan Ding (Environmental Monitoring and Assessment, 2023)

A combined surface-enhanced Raman spectroscopy (SERS)/colorimetric approach for the sensitive detection of malondialdehyde in biological samples - Xiaojun Luo; Shutong Zhang; Zhichao Xia; Rui Tan; Qiuju Li; Ling Qiao; Yi He; Guoqi Zhang; Zhihong Xu (Analytica Chimica Acta, 2023)

Kingella pumchi sp. nov., an organism isolated from human vertebral puncture tissue - Meng Xiao; Ruina Liu; Juan Du; Rui Liu; Lei Zhai; He Wang; Su Yao; Ying-Chun Xu (Antonie van Leeuwenhoek, 2023)

Calculation method and mechanism of ultimate side resistance of screw pile - Hong-wei Ma; Li Liu; Peng Wang; Song Yuan; Qing-rui He; Xiao-li Yang (Marine Georesources & Geotechnology, 2023)

Effect of sulfidation on nitrobenzene removal from groundwater by microscale zero-valent iron: Insights into reactivity, reaction sites and removal pathways - Kai He; Rui Sun; Dezhi Yang; Shuchen Wang; Junjie Shu; Wubo Wan; Ying Pan; Fengyang Qin; Feng He; Liyuan Liang (Chemosphere, 2023)

Soil microbial community structure dynamics shape the rhizosphere priming effect patterns in the paddy soil - Hao Cui; Pengfei Chen; Chao He; Zhenhui Jiang; Rui Lan; Jingping Yang (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Development of quantitative wastewater surveillance models facilitated the precise epidemic management of COVID-19 - Songzhe Fu; Fenglan He; Rui Wang; Wentao Song; Qingyao Wang; Wen Xia; Zhiguang Qiu (Science of The Total Environment, 2023)

Flow-drag reduction performance of a resident electrolytic microbubble array and its mechanisms - Rui Zhu; Huanbin Zhang; Weiqi Wen; Xingyu He; Chenhong Zhao; Yu Liu; Qibin Zhuang; Zhirrong Liu (Ocean Engineering, 2023)

A unified analysis model of FGM double-layered submarine type coupled structure with spectral geometry method - Dongze He; Qingshan Wang; Rui Zhong; Bin Qin (Ocean Engineering, 2023)

Starting up anammox system with high efficiency nitrogen removal at low temperatures: Performance optimization, sludge characterization and microbial community analysis - Liurui Peng; Rui Shi; Youqi Tao; Qian Huang; Maoyuan Yang; Yuecheng He; Wenlai Xu (Journal of Environmental Management, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

Studies on the interaction between homological proteins and anthocyanins from purple sweet potato (PSP): Structural characterization, binding mechanism and stability - Rui Zhang; Shuxin Ye; Ying Guo; Muci Wu; Sijia Jiang; Jingren He (Food Chemistry, 2023)

Combination of pulsed electric field and pH shifting improves the solubility, emulsifying, foaming of commercial soy protein isolate - Rui Wang; Lang-Hong Wang; Qing-Hui Wen; Fei He; Fei-Yue Xu; Bo-Ru Chen; Xin-An Zeng (Food Hydrocolloids, 2023)

Oral administration of Synechococcus sp. PCC7942 trans-vp19 and trans-vp (19+28) genes improve the immune and antioxidant capacity in Procambarus clarkii under white spot syndrome virus stress - Jia Yang; Xiao-Ping Chi; Man Li; Wen-hui He; Rui Jia; Pei-Min He (Fish & Shellfish Immunology, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Rural residents' climate change perceptions, personal experiences, and purchase intention–behavior gap in energy-saving refrigeration appliances in Southwest China - Rui He; Jianjun Jin; Xin Qiu; Chenyang Zhang; Jubo Yan (Environmental Impact Assessment Review, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Study on outdoor thermal comfort of factory areas during winter in hot summer and cold winter zone of China - Xincheng He; Weijun Gao; Rui Wang; Diyang Yan (Building and Environment, 2023)

More intelligent and efficient thermal environment management: A hybrid model for occupant-centric thermal comfort monitoring in vehicle cabins - Xinglei He; Xiaohan Zhang; Rui Zhang; Jiaxin Liu; Xiaoyu Huang; Jinchen Pei; Jingyang Cai; Fen Guo; Yichun Wang (Building and Environment, 2023)

Occurrence, correlation, and partitioning of organophosphate esters in soil and tree bark from a megacity, Western China - Can Wang; Rui-Yu Yuan; Shi-Qiang Wei; Ming-Jing He (Environmental Science and Pollution Research, 2023)

Graphene electrochemical transistor incorporated with gel electrolyte for wearable and non-invasive glucose monitoring - Nan Gao; Rui Zhou; Bo Tu; Tian Tao; Yongqiao Song; Zhiwei Cai; Hanping He; Gang Chang; Yuxiang Wu; Yunbin He (Analytica Chimica Acta, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

An improved cyclic multi model-eXtreme gradient boosting (CMM-XGBoost) forecasting algorithm on the GNSS vertical time series - Zhen Li; Tieding Lu; Xiaoxing He; Jean-Philippe Montillet; Rui Tao (Advances in Space Research, 2023)